Effect of Glu-B3 Allelic Variation on Sodium Dodecyl Sulfate Sedimentation Volume in Common Wheat (Triticum aestivum L.) - Hongqi Si; Manli Zhao; Fuxia He; Chuanxi Ma (The Scientific World Journal)
Sodium dodecyl sulfate (SDS) sedimentation volume has long been used to characterize wheat flours and meals with the aim of predicting processing and end-product qualities. In order to survey the influence of low-molecular-weight glutenin subunits (LMW-GSs) at Glu-B3 locus on wheat SDS sedimentation volume, a total of 283 wheat (Triticum aestivum L.) varieties including landraces and improved and introduced cultivars were analyzed using 10 allele-specific PCR markers at the Glu-B3 locus. The highest allele frequency observed in the tested varieties was Glu-B3i with 21.9% in all varieties, 21.1% in landraces, 25.5% in improved cultivars, and 12% in introduced cultivars. Glu-B3 locus represented 8.6% of the variance in wheat SDS sedimentation volume, and Glu-B3b, Glu-B3g, and Glu-B3h significantly heightened the SDS sedimentation volume, but Glu-B3a, Glu-B3c, and Glu-B3j significantly lowered the SDS sedimentation volume. For the bread-making quality, the most desirable alleles Glu-B3b and Glu-B3g become more and more popular and the least desirable alleles Glu-B3a and Glu-B3c got less and less in modern improved cultivars, suggesting that wheat grain quality in China has been significantly improved through breeding effort.